Response of antioxidant system to formalin in the whole body of rainbow trout, Oncorhynchus mykiss - Ispir, U.; Kirici, M.; Yonar, M. E.; Yonar, S. Mise (C M B Assoc, 2017)
Formalin bath treatments are widely used to control of parasitic infections in aquaculture. However, effects of formaldehyde on the lipid peroxidation and antioxidant system were not still need elucidation. Fish were exposed to formalin at doses of 50, 100 and 200 ppm for 1 h. Fish were then left to depurate for 24 h in formalin-free water. At the end of the test, whole bodies were isolated and homogenized to measured malondialdehyde (MDA) and reduced glutathione (GSH) levels and catalase (CAT) and glutathione peroxidase (GPx) activities. Results obtained showed that formalin significantly (p < 0.05) increased the MDA level. There was statistically significant decrease in the CAT activity of the experimental groups when compared to the control group. After recovery period, the CAT activity was still found to be lower than the control level. The GPx activity and GSH level decreased by formalin exposures and did not return to the control values during recovery periods. From the findings of our study, it can be interpreted that acute formalin inhalation may cause oxidative stress and thus, some secondary toxic effects in whole body.
Keywords: Formalin; Rainbow trout; Oxidative stress; Antioxidant